Nanofibrous composite scaffolds of poly(ester amides) with tunable physicochemical and degradation properties. (July 2015) - Mukundan, Shilpaa; Sant, Vinayak; Goenka, Sumit; Franks, Johnathan; Rohan, Lisa C.; Sant, Shilpa
Graphical abstract: Highlights: Polyester amide elastomer scaffolds mimicking extracellular matrix were fabricated. Scaffold properties can be tuned by varying polymer composition or concentration. Nanofibrous scaffolds exhibited tunable mechanical and degradation properties. Nanofibrous scaffolds enhanced spreading of C2C12 myoblast cells after 6 h. Abstract: Polymeric elastomers like Poly(1, 3-diamino-2-hydroxypropane-co-polyol sebacate) (APS) have gained importance in soft tissue engineering applications due to their tunable mechanical properties and biodegradability. The fabrication of extracellular matrix (ECM)-mimetic nanofibrous scaffolds using APS is however limited due to its poor solubility in commonly used solvents, low viscosity and high temperatures required for thermal curing. In this study, we have overcome these limitations of APS by blending uncrosslinked APS pre-polymer with polycaprolactone (PCL), and have successfully fabricated ECM-mimetic nanofibrous APS scaffolds for the first time. The developed fibrous scaffolds were further characterized for their physicochemical, thermal, mechanical and degradation properties. Effects of APS:PCL weight ratios (0:1, 1:1, 2:1 and 4:1) and total polymer concentration (15–30% w/v) on the fiber morphology, tensile properties, chemical and thermal properties of the APS–PCL composite scaffolds were investigated. Higher APS concentrations in the polymer blend resulted in formation of fused fibers and thus, increased fiber diameters. The degree of hydration and consequently, degradation rate of the scaffolds increased with the APS concentration. The FTIR and DSC studies showed selective loss of APS polymer from composite scaffolds after degradation. Scaffolds with 1:1 APS:PCL ratio exhibited maximum elastic modulus (EM) of 30 ± 2.5 MPa compared to 0:1, 2:1 and 4:1 ratios. Increasing total polymer concentrations (15–30% w/v) at constant (2:1) APS:PCL ratio increased stiffness and tensile strength of the electrospun scaffolds. Biocompatibility studies using C2C12 mouse myoblast cells showed enhanced cell spreading on APS containing scaffolds after 6 h as compared to PCL-only scaffolds. Thus, the present study demonstrates successful development of APS-based thermoset elastomeric nanofibrous scaffolds by blending with semicrystalline PCL polymer for the first time. Tunable physicochemical, mechanical and degradation properties of these composite APS–PCL scaffolds will be further exploited for skeletal muscle tissue engineering applications.